2014
DOI: 10.1200/jco.2013.54.8404
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy in Men With Metastatic Castration-Resistant Prostate Cancer: American Society of Clinical Oncology and Cancer Care Ontario Clinical Practice Guideline

Abstract: Continue androgen deprivation (pharmaceutical or surgical) indefinitely. Abiraterone acetate/prednisone, enzalutamide, or (223)Ra should be offered; docetaxel/prednisone should also be offered, accompanied by discussion of toxicity risk. Sipuleucel-T may be offered to asymptomatic/minimally symptomatic men. For men who have experienced progression with docetaxel, cabazitaxel may be offered, accompanied by discussion of toxicity risk. Mitoxantrone may be offered, accompanied by discussion of limited clinical be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
138
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 50 publications
(18 reference statements)
0
138
0
2
Order By: Relevance
“…Most CRPC patients have metastases at diagnosis or develop widespread disease during the first 2 years of follow-up. First-line chemotherapeutic agents such as docetaxel, and second-line chemotherapy with cabazitaxel, are often toxic and prolong life by only a few months (2). Postchemotherapy androgen deprivation therapy with abiraterone acetate and enzalutamide has been shown to prolong overall survival by only 3.9 and 4.8 mo, respectively, compared with placebo.…”
mentioning
confidence: 99%
“…Most CRPC patients have metastases at diagnosis or develop widespread disease during the first 2 years of follow-up. First-line chemotherapeutic agents such as docetaxel, and second-line chemotherapy with cabazitaxel, are often toxic and prolong life by only a few months (2). Postchemotherapy androgen deprivation therapy with abiraterone acetate and enzalutamide has been shown to prolong overall survival by only 3.9 and 4.8 mo, respectively, compared with placebo.…”
mentioning
confidence: 99%
“…According to the American Society of Clinical Oncology and the Cancer Care Ontario clinical practice guideline, the main option for patients with metastatic CRPC is systemic therapy with docetaxel, with moderate benefit, which is however supported by strong evidence (7). Additionally, the guideline suggests continuation of androgen deprivation indefinitely (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the 2014 version of the European Association of Urology guidelines, DOC may be the treatment of choice for all patients with metastatic CRPC, excluding patients with with a performance status >2 (12). In the 2014 version of the American Society of Clinical Oncology guidelines, Basch et al suggested DOC and prednisone should be offered, but this type of therapy should be discussed with patients at the time of decision-making in relation to the apparently lower risk associated with other options and to the patient's individual circumstances (13). Pre-DOC therapy against CRPC with abiraterone acetate (14) and enzalutamide (15) demonstrated survival and quality-of-life benefits.…”
Section: Discussionmentioning
confidence: 99%